The bioactive of Pinus merkusii needle and bark extract as antioxidantand anti-aging - Febryana Ramadhani; Ermi Girsang; Florenly Florenly (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2021)
Pinus merkusii is a native pine species to Southeast Asia and has used as an oleoresins source and raw material for pulp and paper industries. This plant also possesses several biological activities, such as anti-inflammatory and larvicidal activity. This study aims to evaluate the antioxidant and antiaging activity of P. merkusii needle and bark. The qualitative phytochemical screening was used to evaluate the presence of secondary metabolites compounds. DPPH (2,2-diphenyl-1-picryl-hydrazyl) methods evaluated the antioxidant activity, and an anti-tyrosinase assay was used to evaluate the antiaging activity. Phytochemical analysis showed flavonoids, phenols, alkaloids, tannins, and terpenoids in both extracts. Bark extract showed the presence of saponins and triterpenoids, while needle extract possesses steroids. The antioxidant activity (IC50) of P. merkusii bark extract was 59.32 ± 1.74 µg/mL, stronger than needle extract (68.67 ± 1.47 µg/mL). Also, the bark extract showed higher inhibitory activity of tyrosinase (IC50) 74.97 ± 1.54 µg/mL than needle extract (96.08 ± 1.77 µg/mL). From this investigation, P. merkusii bark extracts appeared to have more potential as a natural source of antioxidants and antiaging and might be beneficial in these subjects.